Increased charge carrier mobility and molecular packing of a solution sheared diketopyrrolopyrrole-based donor–acceptor copolymer by alkyl side chain modification. Issue 12 (8th March 2019) - Hambsch, Mike; Erdmann, Tim; Chew, Annabel R.; Bernstorff, Sigrid; Salleo, Alberto; Kiriy, Anton; Voit, Brigitte; Mannsfeld, Stefan C. B.
Abstract : Side chain extension leads to improved charge carrier mobility in diketopyrrolopyrrole-based donor–acceptor copolymers. Abstract : Semiconducting polymers based on diketopyrrolopyrrole have achieved high charge carrier mobilities in field-effect transistors due to their strong intermolecular interactions, which lead to a high structural order that is beneficial for charge transport. One factor that influences the degree of order in thin films is the choice of solubilizing side chains. In this study, we present a new polymer, poly3-([2, 2′:5′, 2′′-terthiophen]-5-yl)-2, 5-bis(6-dodecyloctadecyl)-2, 5-dihydropyrrolo[3, 4- c ]pyrrole-1, 4-dione-6, 5′′-diyl, which has extended side chains and side-chain branching points that were moved further away from the polymer backbone. Bottom-gate, top-contact field-effect transistors from solution sheared films of this material show average saturation hole mobilities of close to 1 cm 2 V −1 s −1 which is higher than in devices of a commonly used version of this polymer with shorter side chains. The increase in mobility is attributed to an improved structural order in the thin-film state and a decrease in π–π stacking distance. The fabricated devices show very good air-stability without significant degradation in performance after more than one year storage under ambient conditions.